Generation of cDNA libraries : Methods and Protocols; VOL.221 - Ying, Shao-Yao; Ed (Humana Press, 2003)
Presents techniques for generating cDNA/mRNA libraries to identify the functions of specific decoded gene sequences. This title provides a variety of techniques for enhancing the generation of complete and full-length libraries, and for confirming the quality of the cDNAs generated.